Efficacy of guselkumab in subpopulations of patients with moderate‐to‐severe plaque psoriasis: a pooled analysis of the phase III VOYAGE 1 and VOYAGE 2 studies. (14th December 2017) - Gordon, K.B.; Blauvelt, A.; Foley, P.; Song, M.; Wasfi, Y.; Randazzo, B.; Shen, Y.K.; You, Y.; Griffiths, C.E.M.
Summary: Background: Significant advances have been made in the treatment of moderate‐to‐severe plaque psoriasis with biological therapies; however, these agents may not work equally in all populations. Objectives: To evaluate the efficacy of guselkumab in patient subgroups with moderate‐to‐severe psoriasis from the pooled guselkumab VOYAGE 1 and VOYAGE 2 phase III studies. Methods: Using data from the pooled VOYAGE 1 and VOYAGE 2 psoriasis studies, analyses were performed to evaluate the consistency of efficacy [Investigator's Global Assessment (IGA) 0/1 (cleared or minimal psoriasis) and IGA 0 (cleared)] across subpopulations defined by demographics, baseline disease characteristics and previous psoriasis treatment. Results: A total of 1829 patients were randomized. Baseline demographics, disease characteristics and previous psoriasis treatment were comparable across treatment groups in the pooled population. Guselkumab, an anti‐interleukin (IL)‐23 monoclonal antibody that binds to the p19 subunit of IL‐23, provided substantial benefit across almost all subpopulations, with greater proportions of patients achieving IGA 0/1 vs. placebo at week 16, and vs. adalimumab (an antitumour necrosis factor monoclonal antibody) at week 24. Patients treated with guselkumab achieved greater efficacy (IGA 0/1 and IGA 0) compared with adalimumab at week 24 across all weight quartiles, most notably among patients weighing ≥ 100 kg. Conclusions: This analysis demonstrates a high degree of efficacy with guselkumab treatment compared with placebo at week 16 and with adalimumab at week 24 among broad subpopulations of patients with varying baseline demographics, disease characteristics and previous psoriasis treatments. Abstract : What's already known about this topic? Efficacy of biologics may vary among psoriasis subpopulations. What does this study add? Guselkumab achieved superior efficacy vs. adalimumab across all subgroups of patients with psoriasis. Linked Comment: Feldman. Br J Dermatol 2018;178 :22 . Respond to this article